ON THE EFFECTIVE USE OF SOCIOLOGICAL METHODS IN THE ANALYSIS OF THE CORRUPTION LEVEL IN SOCIETY - V. P. Vorob'ev; I. A. Murzina (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2020)
Background. The measurement of corruption, both qualitative and quantitative indicators, is becoming a very important task of sociological science. The effectiveness of any anti-corruption measures is to a large extent determined by the quality of sociological analysis of corruption as a specific social phenomenon, the peculiarities of its real manifestation in modern Russia. In this regard, it is necessary to carefully select and adequately use various sociological methods for measuring the level of corruption. The aim of the study is to consider various approaches and sociological techniques to measuring the level of corruption and to identify their effectiveness. Materials and methods. The work uses methods of traditional analysis of documents, legal acts, scientific literature and statistical information on research issues. Special attention is paid to the analysis of the official methodology of conducting sociological research to assess the level of corruption in the constituent entities of the Russian Federation. Results. The main problems and contradictions of using various sociological methods to measure the level of corruption in modern Russia have been identified. According to the authors, it is difficult to record the level of distribution of the most important corruption manifestations, the specificity of which is the mutual interest of participants of corruption transactions. Conclusions. In order to obtain reliable and realistic information on corruption, an integrated approach using both sociological and psychological methods is needed.